ADSORPSI GAS CO2 DALAM BIOGAS DENGAN ZEOLIT TERAKTIVASI - , Sri subekti, Ir. Siti Syamsiah, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Biogas is the one of the alternative energy which is now being developed as subtitution of the energy derived from organic materials. Component of Biogas most containing methane gases ( CH4), dioxide carbon ( CO2), sulfide hydrogen ( H2S), ammonia ( NH3), hydrogen ( H2), and gas of monoxidecarbon (CO). From component of biogas the which playing a part in determine the quality of biogas is methane gas ( CH4) and dioxide carbon ( CO2). In the biogas production, purification of biogas is the most important thing. The one of methode for biogas purification is adsorption with nature zeolite activation as the adsorbent. The purpose of this research of methane gas concentration and determine effectiveness of adsorber if gas of CO2 gas is adsorpted by natural zeolite activation. It was conducting using the adsorption instrument made of hard pipe containing zeolite active with form palette of measure 1 cm and 2 cm. As free variable of variationcomparison of palette measure and speed of used stream. Measure palette variation is 1 cm and 2 cm, while variation speed of gas stream the used is 2 L / minute and 4 L / minute. For variable tied by is gas concentration of CO2 and of CH4. The result of the study showed that the zeolit active which have in the form of palette of the size 1 cm and speed of gas stream 2L / minute can degrade gas concentration of CO2, but the other of concentration of CH4 not yet can experience of improvement is such as expected.